Sexual reproduction of Hippospongia communis (Lamarck, 1814) (Dictyoceratida, Demospongiae): comparison of two populations living under contrasting environmental conditions - Zarrouk, S.; Ereskovsky, A.V.; Ben Mustapha, K.; Abed, A.E.; Pérez, T. (Marine Ecology, 2013)
The study of the reproductive processes of benthic invertebrates is essential to the understanding of their population dynamics and is also important in formulating conservation plans, especially for exploited species. The sexual reproduction of Hippospongia communis, the ‘honeycomb’ bath sponge, was studied at two locations in the Mediterranean Sea: the Kerkennah Islands (Tunisia, South Mediterranean), where the mean annual seawater temperature is 19 °C, and Marseille (France, Northwestern Mediterranean Sea), where the mean annual water temperature is 16 °C. The aim of this comparative study was to determine whether different environmental conditions could affect reproduction patterns. At both locations, H. communis was found to contain sexual reproductive elements year-round. Oogenesis and embryogenesis occurred throughout the year, whereas spermatogenesis occurred during shorter periods between October and November, in both populations. While gametogenesis seemed to be synchronized, indicating that fertilization could occur at the same time at both locations, spawning was observed in late summer in Marseille, whereas it started in late spring for the Kerkennah population. Larval development of H. communis seems to take longer for sponges living at cooler locations such as Marseille. Reproductive effort calculated for both sexes showed significantly higher values for specimens from Kerkennah Islands. By comparing sexual reproductive patterns of populations living in two contrasted environments, we suggest that a change of thermal regime can affect H. communis phenology.